Multiple myeloma inhibitory effects of natural compounds: enhancement through nanoparticle carriers - Wong, Erica; Staskiewicz, Anna; Pruner, Joshua; Lee, Jean; Tucker, Michael; Smith, Barkley; Rogers, Lanerica; Asuni, Ganiat; Wang, Xinyu (Frontiers in Pharmacology, 2025)
Natural compounds have emerged as promising therapeutic agents for treating cancers such as multiple myeloma (MM). However, poor bioavailability, low stability, and suboptimal targeting often limit their clinical efficacy. Recent advances in nanotechnology have addressed these limitations by utilizing nanoparticle (NP) carriers to enhance the therapeutic potential of natural compounds through improved solubility, stability, and selective delivery to cancer cells. This review explores the inhibitory effects of key natural compounds on MM cells, including 2-cyano-3,12-dioxooleana-1,9-dien-28-oic acid (CDDO) and its derivatives, caffeic acid phenethyl ester (CAPE) and its derivatives, xanthohumol (XN) and its derivatives, resveratrol (RSV) and its derivatives, curcumin (CUR), 3,4,5-trihydroxybenzoic acid (gallic acid; GA), and evodiamine (EVO). These compounds exhibit potent anti-proliferative, pro-apoptotic, and anti-inflammatory properties through the modulation of signaling pathways such as NF-κB, STAT3, and PI3K/Akt, which are critical in MM pathogenesis. Despite their therapeutic promise, the clinical application of these natural agents has been hampered by pharmacokinetic challenges. NP carriers, including liposomes, polymeric NPs, and lipid-based nanocarriers, have been engineered to improve these compounds’ bioavailability and targeted delivery, enhancing their cytotoxicity against MM cells. For instance, CDDO and its derivatives encapsulated in NPs have demonstrated increased intracellular accumulation and improved inhibition of NF-κB activity. Similarly, NP formulations of CAPE, XN, and RSV have enhanced anti-MM effects through improved stability and sustained drug release. CUR, known for its poor water solubility, has seen its therapeutic potential augmented through NP delivery systems, enabling higher drug concentrations at tumor sites. Though structurally distinct, GA and EVO have benefited from NP-based enhancement, exhibiting improved bioavailability and selective targeting of MM cells. This review highlights the promising role of NP carriers in overcoming the pharmacokinetic limitations of natural compounds, offering new avenues for more effective MM therapies.